Draft Sixth Five Year Plan 1980-85 and 81-82 (Statements) Vol. III - Planning Commission (Planning Commission, 1980)
Summary statement of outlays and expenditure Schemewise outlays and expenditure Selected Physical Targets and Achievements Minimum Needs Programme Centrally Sponsored Schemes Command Area Development (CAD 1-8) Irrigation and Flood Control (IF-1-19) Power.
Planning Department